An integrated transcriptome and metabolome analysis reveals the gene network regulating flower development in Pogostemon cablin - Zhang, Chan; Liu, Xiaofeng; Liu, Ya; Yu, Jing; Yao, Guanglong; Yang, Huageng; Yang, Dongmei; Wu, Yougen (Frontiers in Plant Science, 2023)
Pogostemon cablin is a well-known protected species widely used in medicine and spices, however the underlying molecular mechanisms and metabolite dynamics of P. cablin flower development remain unclear due to the difficulty in achieving flowering in this species. A comparison of the transcriptome and widely targeted metabolome during P. cablin flower development was first performed in this study. Results showed that a total of 13,469 differentially expressed unigenes (DEGs) and 371 differentially accumulated metabolites (DAMs) were identified. Transcriptomic analysis revealed that the DEGs were associated with starch and sucrose metabolism, terpenoid biosynthesis and phenylpropanoid biosynthesis. Among these DEGs, 75 MIKC-MADS unigenes were associated with the development of floral organs. Gibberellins (GAs), auxin and aging signaling might form a cross-regulatory network to regulate flower development in P. cablin. According to the metabolic profile, the predominant DAMs were amino acids, flavonoids, terpenes, phenols, and their derivatives. The accumulation patterns of these predominant DAMs were closely associated with the flower developmental stage. The integration analysis of DEGs and DAMs indicated that phenylpropanoids, flavonoids, and amino acids might be accumulated due to the activation of starch and sucrose metabolism. Our results provide some important insights for elucidating the reproductive process, floral organ, and color formation of P. cablin flowers at the molecular level. These results will improve our understanding of the molecular and genetic mechanisms involved in the floral development of P. cablin.